Fasilitas Pendidikan Kuliner Di Pekanbaru Dengan Pendekatan Arsitektur Metafora - Tivany, Olivia Rizki; Aldy, Pedia; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Culinary is a promising venture, can be seen from the large number of restaurants, cafes, and hotels that serve many interesting culinary. Growing number of culinary bussiness makes profesional chef much in need, but the facilities for study to become a professional chef is not yet available in the city of Pekanbaru. Culinary education facilities is a culinary educational spaces that are expected to facilitate the development of culinary activities where there is a non-formal education classes such as cooking course in theory or practice, seminars, and research. Culinary Education Facilities with Tangible Metaphor design approach aiming so that when people see the building will recognize the function of the building. As of the result of this design concept with the Frying Pan where the kitchen tool usage techniques is often known to public by stir frying. Culinary education facility provides the most important culinary education classes about teaching in kitchen (cooking class), pastry and bakery class, cooking class for kids, demontration class, and more. In additional also available supporting facilities such as dormitories for students, entertaiment room, lounge area and shower room. Key word: Metaphor Architecture, Culinary, Culinary Education